Some Remarks on Generalized Metric Spaces of Branciari - Kumam, Poom; Dung, Nguyen Van (Sarajevo Journal of Mathematics, 2024)
In this paper, we prove some properties of a generalized metric space in the sense of Branciari. As applications, we correct some confusion about this space in the literature. Examples are given to illustrate the results. 2010 Mathematics Subject Classification. Primary 46A16, 54H25; Secondary 54D99, 54E99